1998
DOI: 10.2165/00003088-199834010-00001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics and Pharmacodynamics of Torasemide

Abstract: The new loop diuretic torasemide belongs to the pyridine sulfonylurea class. It is well absorbed and yields a bioavailablity of about 80% in healthy individuals, even higher in patients with oedema. This is roughly double that of the 'classical' loop diuretic furosemide (frusemide) [26 to 65%]. Torasemide is highly bound to protein (99%) as is furosemide. The volume of distribution of torasemide was determined as 0.2 L/kg as compared with 0.11 to 0.18 L/kg for furosemide. Torasemide undergoes extensive hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
70
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 47 publications
9
70
0
1
Order By: Relevance
“…Approximately 20% of torsemide is eliminated unchanged in the urine, whereas M1 and M5 comprise 10 and 50% of a torsemide dose excreted renally, respectively (Miners et al, 1995;Knauf and Mutschler, 1998). A human study showed 1.5-, 1.7 and 2.8-fold higher torsemide AUCs with the CYP2C9*1/*3, *2/*3, and *3/*3 genotypes, respectively, whereas those with the *1/*2 genotype behaved similarly to the wild type (Vormfelde et al, 2004).…”
Section: B Cyp2c9mentioning
confidence: 99%
“…Approximately 20% of torsemide is eliminated unchanged in the urine, whereas M1 and M5 comprise 10 and 50% of a torsemide dose excreted renally, respectively (Miners et al, 1995;Knauf and Mutschler, 1998). A human study showed 1.5-, 1.7 and 2.8-fold higher torsemide AUCs with the CYP2C9*1/*3, *2/*3, and *3/*3 genotypes, respectively, whereas those with the *1/*2 genotype behaved similarly to the wild type (Vormfelde et al, 2004).…”
Section: B Cyp2c9mentioning
confidence: 99%
“…A quantification of torasemide and its metabolites in urine revealed 21 to 25% torasemide, 11% M1, 3% M3, and 34 to 44% M5, resulting in a total renal clearance of Ͼ80% for torasemide and its metabolites. 2,6 The calculated renal clearance of free torasemide (not bound to plasma protein) was approximately 640 ml/min, 3 which is equal to renal plasma flow. The high clearance for torasemide indicated the involvement of active secretory mechanisms in proximal tubule cells.…”
mentioning
confidence: 99%
“…In contrast, the classical loop diuretic furosemide has a bioavailability of only 26 to 60%. 2,3 Torasemide is highly bound to plasma proteins, and its elimination half-life is almost 6 h, which is approximately three-fold higher than that of furosemide or bumetanide. Torasemide shares a similar mechanism of inhibition of Na ϩ -K ϩ -2Cl Ϫ reabsorption at the thick ascending limb of Henle's loop with furosemide or bumetanide.…”
mentioning
confidence: 99%
See 2 more Smart Citations